Performance Factors in a Mountain Ultramarathon - Balducci, Pascal; Clémençon, Michel; Trama, Robin; Blache, Yoann; Hautier, Christophe (International Journal of Sports Medicine, 2017)
This study aimed to determine mountain ultra-marathon (MUM) performance factors in a large group of endurance mountain runners. Maximal aerobic speed (MAS) was assessed one week prior to the MUM. The level and graded (10%) energy cost of running, stiffness, knee extensors force (KEf), and jump height on a counter movement jump (CMJ) were measured in 24 male ultra runners before (pre) and immediately after (post) the Interlacs Trail (75 km and 3 930/3 700 m d+/d−). Performance time was correlated with MAS (r=− 0.74, p<0.001), fraction of MAS (FMAS) sustained (r=− 0.89, p<0.001), KEf (r=− 0.51, p<0.05), and KEf loss (r=− 0.51, p<0.05). A multiple regression analysis was performed using performance time in minutes (T) and the calculated individual characteristics, resulting in T=− 11.852×FMAS−37.195×MAS−0.118×KEf+2090.581 (R2=0.98, with 95% confidence interval). Contrary to expectations, performance was neither correlated to the level or uphill energy cost of running nor to the changes of these costs post-MUM. To perform in a MUM, training should take into account muscle strength of the KE, MAS and FMAS.
Keywords: trail running; running economy; step frequency; isometric force; energy cost of running